Utilização de modelo matemático de qualidade da água para análise de alternativas de enquadramento do rio Vacacaí Mirim - Oppa, Lorenza Ferreira (2007)
Searching for economical development, the society uses water in an abusive way; hence, demanding the water resources management. The use of mathematical models, which simulate the water quality conditions, becomes a key tool to quantify the self depuration capacity of the river. This research aims to assess classification proposals to the hydrographic region of the Vacacaí Mirim River, using the mathematical model of water quality QUAL2E as a supporting tool. The preponderant utilizations of the region were the public supply, temporary and stable agriculture culture, cattle and recreation. The data to calibrate the model were obtained from three water sampling campaigns. The simulated parameters were: dissolved oxygen (DO), biochemical oxygen demand (BOD), fecal coliform, nitrite, nitrate and dissolved phosphorus. The prognostic simulations were made to the flows Q80, Q90 and Q95; in the natural conditions and in the water demand conditions to irrigation. In the calibration, it was verified the water quality of the Vacacaí Mirim River presents good conditions. Despite the initial parts considered in the model, where the concentration values surpass the established limits to the class 2 and 3 of the Resolution n°357/05 of the CONAMA, for all the parameters. In the prognostic, the results exceeded the classes limits, mostly with the flow Q95, in various parts. The classification alternatives suggested regarding the usage of water in the region and model simulations are: class 3 to the first three portions of the river, indicating as main solution the wastewater treatment in these parts, and class 2 to the rest of the river; and class 2 for the whole river.